An Addressable 2D Heterogeneous Nanoreactor to Study the Enzyme‐Catalyzed Reaction at the Interface. Issue 43 (22nd June 2017) - Wang, Dianming; Zhang, Guoliang; Zhang, Yiyang; Xin, Ling; Dong, Yuanchen; Liu, Yang; Liu, Dongsheng
Abstract: Membrane plays significant role in cellular enzymatic reactions. To better understand its function on membrane integral or bound enzymes, DNA origami and frame‐guided assembly strategy are combined to construct a given‐size, addressable enzyme‐containing nanomembrane as a heterogeneous reactor to explore the enzymatic catalyst reaction on the membrane. The enzymes in the membrane are located precisely. This new kind of membrane can enrich hydrophobic substrate molecules in aqueous solution to the embedded enzymes. Otherwise, this nanomembrane shows the capability of substrate selectivity, which plays important role in the highly efficient and specific properties of enzymes in vivo. Abstract : DNA origami and a frame‐guided assembly strategy are combined to construct a given‐size, addressable enzyme‐containing nanomembrane as a heterogeneous reactor to explore the enzymatic catalyst reaction on membranes. The enzymes in the membrane are located precisely. This membrane can enrich hydrophobic substrate molecules in aqueous solution to the embedded enzymes. Moreover, it shows the capability of substrate selectivity.